Stereotype of Racial issue on #starterpack - Hakeemi Harris Ayedoji (Universitas Ahmad Dahlan, 2021)
Semiotic comes from the Greek word, which is semeion (sign). Nevertheless, generally, semiotics is a study which concerns about the existence of sign in society. We could find signs everywhere in the form of words, images, and also objects. According to Pierce’s study, something could be categorized into signs if it could be taken apart in the triadic relation. The primary data of this research is the #starterpack tweets on Twitter. The data used is focused on the #starterpack tweets with white and black people context. To collect the data, the researcher used the observation method and used note technique. From the analysis, the researcher #starterpack tweets with mainly four images in them. All the data are analyzed with the triadic signs, which are signs, objects, and interpretations. The signs analyzed show objects and interpretations that lead to the gap between white and black people. Those gaps then lead to stereotypes of white and black people.